Pengaruh Disiplin Kerja, Pelatihan Kerja Dan Motivasi Terhadap Kinerja Karyawan - Sarton Sinambela; Parel Naibaho; Erwin Simanjuntak; Gilang Wijiangkara (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2021)
This Study aims to see relationship between work discipline, job training, and motivation towards employee performance at PT. Karya Indah Multiguna. The data used in this study are primary data obtained from 86 respondents who have filled out a questionnaire. This study uses multiple linear regression analysis, hypothesis testing with the t-test and f-test methodes and to see the determinant coefficien. The test result of multiple linear regreession analysis : X1 sig value (0,001<0,05), then HA is accepted which means that there is a significant effec of work discipline on employee performance, X2 (0,001<0,05) then HA is accpeted which means there is a significant effect on job traning performance, and X3(0,000<0,05) then HA is accepted which means that there is a significant effect of motivation on performance. The results of the research simultaneosly show that f count > f table with results (168,842>2,715) so simultaneously work discipline, job training and motivation have a simultaneous effec on perfomance.